Neoaulonastus sidorchukae, a new species of quill mites (Acariformes: Syringophilidae) associated with the purple-rumped sunbird Leptocoma zeylonica (Linnaeus) (Passeriformes: Nectariniidae) from Sri Lanka - Zmudzinski, Mateusz; Skoracki, Maciej; Hromada, Martin (Zootaxa, 2019)
A new quill mite species, Neoaulonastus sidorchukae sp. nov. (Acariformes: Syringophilidae), is described from under-tail covert feathers of Leptocoma zeylonica (Linnaeus) (Passeriformes: Nectariniidae) from Sri Lanka. It is the second record of syringophilid mites of the genus Neoaulonastus parasitizing sunbirds.